The lucky lottery - Roy, Ron, 1940-; Gurney, John (New York : Random House, 2000)
Dink and his two friends help Lucky find the culprit who stole Lucky's winning lottery ticket
"A Stepping Stone book."
Keywords: Lotteries -- Fiction; Mystery and detective stories